Expression of ALDH and SOX-2 in Pulmonary Sclerosing Pnemocytoma (PSP) of the Lung: Is There a Meaning Behind? - Aramini, Beatrice; Masciale, Valentina; Manfredini, Beatrice; Bianchi, Daniel; Banchelli, Federico; D'Amico, Roberto; Bertolini, Federica; Dominici, Massimo; Morandi, Uliano; Maiorana, Antonino (Frontiers in Medicine, 2020)
Background. Pulmonary sclerosing pneumocytoma (PSP) is a rare benign pulmonary tumor that derives from primitive respiratory epithelium of the pulmonary alveolus. The etiology and pathogenesis are still unclear. Histopathological diagnosis focuses on cells that are positive for TTF1, EMA, cytokeratin-7 and CAM 5.2. The aim of our study is to highlight the elevated expression of ALDH and the presence of SOX-2 in pulmonary sclerosing pneumocytoma. Methods. We report five cases of pulmonary sclerosing pneumocytoma undergone surgery at our Division of Thoracic Surgery, during a period between 1994 and 2011. ALDH and SOX-2 markers were also tested for positivity in all the patients. Results. Patients showed elevated expression of ALDH during immunohistochemistry and mild expression of SOX-2, although in two cases in which SOX-2 was highly expressed. Among these two patients, one presented with lymph node recurrence while the other had no recurrence with a PET-positive nodule. In particular, the patient who had developed recurrence had an ALDH score of 4 and a SOX-2 score of 3, whereas the patient with the PET-positive nodule showed an ALDH score of 4 with a mild SOX-2 expression of score 1. Conclusions. This is the first attempt demonstrating the elevated expression of ALDH in this disease. SOX-2 expression was noted in both the patient who developed recurrence and the patient with a PET-positive nodule. We believe that further investigation may be highly useful to better characterize these two markers as well as understand their function.